An urgent need to tackle the maternal obesity epidemic. (16th November 2010) - Candelier, CK; O'Brien, J; Bird, A
Abstract : In our maternity unit, the incidence of women with gestational diabetes (GDM) has increased over the years without a corresponding increase in the incidence of women with pregestational (type 1 and 2) diabetes, the ratio being 2 to1 in 2002 and 5 to 1 in 2009. The Caesarean section rate (CSR) in women with GDM is high and now approaches the CSR in women with pregestational diabetes. During this period, no babies born to women with pregestational diabetes had birth weights >4.5 kg while the mean incidence in birth weight >4.5kg was 3.1% in babies born to women with GDM. Maternal obesity, an important screening risk factor for gestational diabetes, is increasing in prevalence among our pregnant population. In 2008, 60% of women with GDM had a booking body mass index (BMI) > 30 compared to 13.5% of our overall pregnant population. Studies like the 2008 HAPO study have shown that maternal hyperglycaemia and maternal obesity are independent risk factors for adverse pregnancy outcomes such as delivery by Caesarean section and babies born with higher birth weights. The increasing prevalence of obesity in young pregnant women is draining overstretched healthcare resources. Women with GDM must adopt major lifestyle changes (healthy eating, diet, exercise) to reduce their risk of developing GDM in future pregnancies, type 2 diabetes and cardiovascular disease. Abstract PM77 Caesarean section rate 2005 2006 2007 2008 2009 Pregestational diabetes 57.1% 63.2% 64.3% 50.0% 55.6% Gestational diabetes 28.1% 31.6% 52.0% 40.4% 46.4% Overall CSR 26.7% 23.1% 25.2% 24.7% 23.4